The Impact of Nonbreaking Waves on Wind‐Driven Ocean Surface Turbulence. Issue 1 (8th January 2020) - Savelyev, I. B.; Buckley, M. P.; Haus, B. K.
Abstract: A comprehensive study on the properties of upper ocean turbulence and its response to a variety of wind and wave forcing conditions was conducted at the Surge Structure Atmosphere INteraction (SUSTAIN) facility, University of Miami, RSMAS. The dimensions of SUSTAIN wind‐wave‐current tunnel are 18 m long, 6 m wide, and 2 m high, uniquely allowing for freely forming turbulence unconstrained by side walls. The grid of input parameters covered a range of wave steepness ( ak : 0–0.27) within each investigated wind speed ( U 10 : 2–20 m/s), allowing for the isolation of wave effects on the turbulence driven by both wind and waves. The response of turbulence to each pair of wind‐wave parameters was measured in steady‐state conditions (after 20+ min of settling time) by a suite of nonintrusive turbulence visualization techniques, located at 10 m fetch. These included 3‐D visualization of water tracing dye entrainment by turbulence, underwater particle image velocimetry, and passive and active thermal imagery resolving surface skin temperature and velocity fluctuations. The resulting data set includes both qualitative 3‐D view of subsurface turbulent structures and precise quantitative turbulent kinetic energy (TKE) measurements mapped out in response to the grid of input parameters. In lower winds, TKE was found to grow substantially in response to increasing wave steepness, in line with the expected effect of increasing wave forcing. However, in higher winds the effect of increasing wave steepness on TKE was found to be negative. It is hypothesized to be due to the rise of airflow separation, effectively sheltering much of the water surface from turbulence production by wind friction. Key Points: While subjected to a set of fixed wind speeds, the impact of waves on surface turbulence was isolated, visualized, and quantified In lower wind cases, as expected, increased wave steepness energized Langmuir‐type turbulent structures In higher winds, steepening waves were found to dampen surface turbulent kinetic energy, possibly due to airflow separation Plain Language Summary: This laboratory study aims to visualize and quantify small‐scale turbulence taking place below the ocean surface. Of a particular interest here is the effect of surface wave motion, outside of wave breaking, and how it influences ocean turbulence, which is otherwise forced by wind. Unlike in the field, the laboratory setup allows independent control of wind and wave parameters, thus allowing decomposition of wind‐ and wave‐driven aspects of the turbulent flow. A mixture of well‐known and novel nonintrusive turbulence visualization techniques employed in this study gave unprecedented clear view of turbulent response under varying forcing conditions. Two major counteracting wave‐dependent processes were found to impact surface turbulence. One is additional turbulence production due to the action of wave induced drift current, another is turbulence dampening due wave induced airflow separation, causing a reduction in wind friction.